Family planning, reproductive health and pregnancy after bariatric surgery: a survey of bariatric healthcare professionals in Switzerland - Ioannis I. Lazaridis; Sofya Lukovnikova; Georgios Peros; Andreas Andreou; Diana Mattiello; Thomas Köstler; Dimitrios Schizas; Urs Zingg; Claudia Cavelti-Weder; Tarik Delko (Swiss Medical Weekly)
AIMS: A wide range of reproductive health issues, including fertility, pregnancy outcomes and contraceptive practices can be affected by morbid obesity and weight loss subsequent to bariatric surgery. This study aimed to explore the attitudes and practices of bariatric healthcare professionals in Switzerland regarding reproductive health counselling in the context of bariatric surgery.